Exclusão de amônio está relacionada à senescência foliar e à partição de nitrogênio em plantas de arroz - Sousa, Rikaely Torres de (2018)
Nitrogen (N) is a fundamental macronutrient for plants and a determinant factor that determines the production of vegetal biomass. In the micromolar concentration range, the roots of most species prefer the absorption of ammonium to nitrate, whereas in those of millimolar, ammonium often causes toxicity. Rice is one of the species that can be improved in the presence of high concentrations of ammonium, however, as rice tolerance strategies are very important. Especially, the dynamics of leaf senescence and an ammonium partition and other forms of N expression among different ways of projecting themselves to a high degree of long-term exposure are completely unknown. In order to investigate the physiological, morphological and biochemical mechanisms of rice for the excess of plants, rice plants (Oryza sativa japonica cv. Nipponbare) were cultivated in two contrasting conditions of nitrogen source, 15 mM NO3- (reference) or 15 mM of NH4+ during 56 days and evaluated in terms of growth, photosynthesis, redox metabolism, as well as partitioning of biomass and partition of the different forms of nitrogen. Plants cultivated in the presence of high ammonium presented restriction of root growth, but they maintained unchanged shoot growth and photosynthetic activity when compared to control. In addition, rice plants grown in high ammonium present accumulation of the toxic form in culm and senescent leaves, preserving the root and the photosynthetic apparatus of young leaves. In the roots, the highest GPOD activity was observed in parallel to the unchanged H2O2 content and a decrease in the indicators of lipid peroxidation, thus suggesting an effective antioxidative protection in this tissue, despite growth restriction. The data presented suggest that the partition of nitrogen between senescent leaves, culm and green leaves possibly represents an important mechanism of exclusion of ammonium and preservation of the photosynthetic apparatus. In parallel, the increase of GPOD activity in plants grown in high ammonium may suggest an important role of these enzymes in the removal of excess EROS (reactive oxygen species) and in the control of root growth